Pathology of Editing in Persian Literature Books of High School - Mohammad Reza Pashaei; Saeed Ghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The subject of editing textbooks is a scientific perspective that can be pathologic and it is the title of this article. According to the title of the article, the purpose of this essay is the expression of some problems and shortcomings in the field of editing Persian textbooks of the High school as a statistical society. It is in structure, deductive reasoning, and the evidence has been used by the statistical sample method. Each year, the group of educational books reviews these books generally or partially, the exact review of the editorial team in the field of editing the textbooks is also highly felt. Therefore, some of the relevant issues were mentioned in three areas of editing, namely linguistic, content, and technical. We discussed the important issues which needed to be addressed by the editor in these books. The result of this research suggests that among the three editing areas mentioned in the editing books, most of the drawbacks are in the “technical editing” and these books need a comprehensive overview in this particular editorial area.